Differences In The Effectiveness Of Abpk And Klop Kb Counseling Against Kb Mkjp Elections - Sri Wahyuningsih; Feva Tridiyawati (CV. Inara, 2023)
According to the United States Census Bureau, the world population in 2021 will be 74 million people. In Asia in 2021 the population will reach 4.688 billion. While Indonesia ranks fourth with the largest population in the world of 273.5 million people. The impact of the population explosion is increasing poverty and hunger, malnutrition in children under five, maternal and child mortality, increased unemployment. One of the methods used to reduce the rate of population growth is through birth control by means of family planning. There are two types of Family Planning Counseling Modules, namely using a Family Planning Decision Making Tool and screening of medical eligibility criteria for contraceptive use (KLOP Wheel). Knowing the differences in the effectiveness of ABPK and KLOP KB counseling on the selection of KB MKJP. Analytics with cross sectional design. The sample in this study were all family planning acceptors at the Pasir Jaya Tangerang Health Center in October 2022 as many as 56 people, the sampling technique was total sampling. Most of the respondents were aged 20-35 years (62.5%), secondary education (50.0%) and multiparous parity (89.3%). The family planning acceptors in the ABPK counseling group mostly chose injections 53.6%, and in the KLOP counseling group most chose the IUD 78.6%. There is a difference in the effectiveness of ABPK and KLOP KB counseling on the selection of KB MKJP (p.value 0.001). There is a difference in the effectiveness of ABPK and KLO KB counseling on the selection of KB MKJP (p.value 0.001). For family planning acceptors, they should be able to carefully consider the choice of contraceptives in order to be able to determine the choice of long-term family planning methods (MKJP).